2018
DOI: 10.1111/cen.13720
|View full text |Cite
|
Sign up to set email alerts
|

Young age is associated with increased rates of residual and recurrent paediatric differentiated thyroid carcinoma

Abstract: Despite comparable apparent initial disease burden and treatment, younger children have poorer outcomes when compared to adolescents, even in the absence of nodal metastases and thus may warrant intensification of primary therapy and/or tumour surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
4
7
0
Order By: Relevance
“…12,21 Lastly, we had nearly a 5:1 female predominance, similar to previous studies. However, a score ≥2 had good specificity for detecting thyroid cancer (85.1%) though the sensitivity was poor (22.7%).…”
Section: Clinical Featuressupporting
confidence: 88%
See 1 more Smart Citation
“…12,21 Lastly, we had nearly a 5:1 female predominance, similar to previous studies. However, a score ≥2 had good specificity for detecting thyroid cancer (85.1%) though the sensitivity was poor (22.7%).…”
Section: Clinical Featuressupporting
confidence: 88%
“…While young age is associated with a higher chance of persistent disease or recurrence, we did not find it affected the likelihood of malignancy, though it is thought that young children overall may have worse outcomes compared to adolescents given the same cancer burden. 12,21 Lastly, we had nearly a 5:1 female predominance, similar to previous studies. 9,22,23 We did find a significant difference in TSH levels between patients with malignant and benign nodules.…”
Section: Clinical Featuressupporting
confidence: 88%
“…Despite the findings of these studies, some authors found no association between puberty and clinical and pathological features in DTC ( 10 , 25 ). In agreement with previous studies ( 5 , 21 , 22 , 26 , 27 ), structural disease at the end of follow-up was more prevalent in prepubertal patients, despite no difference in the long-term disease-free survival rate.…”
Section: Discussionsupporting
confidence: 92%
“…Other authors have also shown increased aggressiveness at presentation in patients diagnosed with DTC before puberty ( 4 , 5 , 6 , 20 , 21 , 22 , 23 , 24 ). In a sample of 27 pediatric patients, including 10 prepubertal patients, Lazar et al found nodal metastasis at diagnosis in all prepubertal patients and distant metastasis in 70% of them ( 4 ).…”
Section: Discussionmentioning
confidence: 81%
“…Differentiated thyroid carcinoma is frequently more advanced at diagnosis in pre-pubertal children when compared to adolescents and adults, although the long-term prognosis is highly favourable for both children and adolescents [ 79 , 80 , 81 ].…”
Section: Differentiated Thyroid Carcinoma (Dtc)mentioning
confidence: 99%